Teori Belajar Pemrosesan Informasi M. Gagne - A Nasih Ahbab; Endang Sri Wahyuni (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The information processing learning theory offers a cognitive framework that explains how individuals receive, process, store, and retrieve information during the learning process. This study aims to understand how this theory can be applied to design more effective, student-centered learning strategies. Using a literature review approach and theoretical analysis, the study explores key cognitive stages in the learning process and influencing factors such as attention, motivation, and cognitive engagement of students. The findings reveal that the information processing theory can enhance our understanding of how students learn and provide insights for creating a learning environment that better supports the learning process. While the theory is valuable in explaining cognitive aspects of learning, it has limitations in accommodating affective and social dimensions. Therefore, this study suggests the need to integrate information processing theory with other, more holistic learning approaches. Further research is proposed to develop more comprehensive learning methods by considering the interaction between cognitive processes and affective factors, as well as the development of more adaptive teaching tools